2008
DOI: 10.1093/cercor/bhm244
|View full text |Cite
|
Sign up to set email alerts
|

Brain Size and Cortical Structure in the Adult Human Brain

Abstract: We investigated the scale relationship between size and cortical structure of human brains in a large sample of magnetic resonance imaging data. Cortical structure was estimated with several measures (cortical volume, surface area, and thickness, sulcal depth, and absolute mean curvature in sulcal regions and sulcal walls) using three-dimensional surface-based methods in 148 normal subjects (n [men/women]: 83/65, age [mean +/- standard deviation]: 25.0 +/- 4.9 years). We found significantly larger scaling expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
259
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(298 citation statements)
references
References 69 publications
35
259
1
3
Order By: Relevance
“…Indeed, volumetric studies have always reported reduced cortical volume in the syndrome (Eliez et al, 2000;Kates et al, 2004Kates et al, , 2001Simon et al, 2005;van Amelsvoort et al, 2001). If cortical volume is undeniably the product of its surface and thickness, surface changes are more susceptible to result in volumetric changes than thickness alterations (Im et al, 2008). Thus, the drastic cortical surface reduction that we observed in previous studies (Schaer et al, 2006 may better predict the decreased volume than subtle thickness changes associated with maturation.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, volumetric studies have always reported reduced cortical volume in the syndrome (Eliez et al, 2000;Kates et al, 2004Kates et al, , 2001Simon et al, 2005;van Amelsvoort et al, 2001). If cortical volume is undeniably the product of its surface and thickness, surface changes are more susceptible to result in volumetric changes than thickness alterations (Im et al, 2008). Thus, the drastic cortical surface reduction that we observed in previous studies (Schaer et al, 2006 may better predict the decreased volume than subtle thickness changes associated with maturation.…”
Section: Discussionmentioning
confidence: 63%
“…A number of studies have suggested that head size (e.g., ICV) covaries with gray and white matter volume and cortical surface area, but generally not with GM thickness [Im et al, 2008; Pakkenberg and Gundersen, 1997]; accordingly, participant gender was used instead of ICV as a nuisance variable for statistical analyses of GM thickness [Barnes et al, 2010]. The results of this report remained qualitatively similar when using both covariates in statistical models.…”
Section: Methodsmentioning
confidence: 99%
“…It shows that handling ICV differences in folding studies may not be as simple as including ICV as a covariate in the underlying statistical test. This paper proposes two systematic methods for handling ICV changes in folding studies using the proposed descriptor and shows that while the findings using one method are consistent with [10], those using the other method are consistent with [11,12].…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, while one study [10] using the fractal-dimension (FD) measure reported higher complexity in adult females, two very recent studies [11,12] using the isoperimetric ratio (IPR) measure report higher complexity in larger adult brains (i.e. males).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation